Blockade of Pannexin-1 Channels and Purinergic P2X7 Receptors Shows Protective Effects Against Cytokines-Induced Colitis of Human Colonic Mucosa - Diezmos, Erica F.; Markus, Irit; Perera, D. S.; Gan, Steven; Zhang, Li; Sandow, Shaun L.; Bertrand, Paul P.; Liu, Lu (Frontiers in Pharmacology, 2018)
Introduction. The pannexin-1 (Panx1) channels are found in many cell types, and ATP released from these channels can act on nearby cells activating purinergic P2X7 receptors (P2X7R) which lead to inflammation. Although Panx1 and P2X7R are implicated in the process of inflammation and cell death, few studies have looked at the role they play in inflammatory bowel disease in human. Hence, the aim of the present study was to investigate the function of Panx1 and P2X7R in an ex-vivo colitis model developed from human colonic mucosal explants. Materials and Methods. Healthy human colonic mucosal strips (4 × 10 mm) were incubated in carbogenated culture medium at 37°C for 16 h. Proinflammatory cytokines TNFα and IL-1β (each 10 ng/mL) were used to induce colitis in mucosal strips, and the effects of Panx1 and P2X7R on cytokines-induced tissue damage were determined in the presence of the Panx1 channel blocker 10Panx1 (100 µM) and P2X7R antagonist A438079 (100 µM). The effects of 10Panx1 and A438079 on cytokines-enhanced epithelial permeability were also studied using Caco-2 cells. Results. Histological staining showed that the mucosal strips had severe structural damage in the cytokines-only group but not in the incubation-control group (P < 0.01). Compared to the cytokines-only group, crypt damage was significantly decreased in groups receiving cytokines with inhibitors (10Panx1, A438079, or 10Panx1 + A438079, P < 0.05). The immunoreactive signals of tight junction protein zonula occludens-1 (ZO-1) were abundant in all control tissues but were significantly disrupted and lost in the cytokines-only group (P < 0.01). The diminished ZO-1 immunoreactivity induced by cytokines was prevented in the presence of 10Panx1 (P = 0.04). Likewise, 10Panx1 significantly attenuated the cytokines-evoked increase in paracellular permeability of Caco-2 cells. Although the inhibition of P2X7R activity by A438079 diminished cytokines-induced crypt damage, its effect on the maintenance of ZO-1 immunoreactivity and Caco-2 epithelial cell integrity was less evident. Conclusions. The blockade of Panx1 and P2X7R reduced the inflammatory cytokines-induced crypt damage, loss of tight junctions and increase in cell permeability. Thus, Panx1 and P2X7R may have roles in causing mucosal damage, a common clinical feature of inflammatory bowel disease.